The Potency of Noni Leaves Extract (Morinda citrifolia L.) as a Bioreductor in the Synthesis of Copper Nanoparticles and Its Effectiveness as an Antibacterial against Streptococcus pyogenes - Retno Wahdany Huda Putri; Suyatno Sutoyo (Jurnal Kimia Sains dan Aplikasi, 2025)
The noni (Morinda citrifolia L) is one of Indonesia’s traditional medicinal plants, which people have widely used to treat dysentery, hypertension, diabetes, and heart attacks and prevent cancer. The noni contains phenolic compounds, namely flavonoids, anthraquinones, alkaloids, and tannins, which have the potential to act as bioreductors. The research aims to synthesize copper nanoparticles (CuNPs) using noni leaves extract as a bioreductor and assay their antibacterial activity. CuNPs were synthesized by mixing noni leaf extract and copper sulfate in a 1:1, 1:2, 1:3, and 1:4 ratio. It was characterized using UV-Vis, PSA, FTIR, and XRD. Antibacterial activity was tested using the disc diffusion method on Streptococcus pyogenes. The results showed that the optimum synthesis of CuNPs was at a ratio of 1:3 and pH 10. CuNPs had a maximum UV-Vis absorption wavelength at 305 nm, an average particle size of 5.46 nm with a polydispersity index (PDI) of 0.2048, and the Cu-O peak was observed at 560 cm-1 in the FTIR spectrum. XRD measurements revealed peaks at 2θ angles of 43.38°, 50.50°, and 74.43°. CuNPs showed good potential as an antibacterial agent against Streptococcus pyogenes with an average inhibition zone diameter of 17.3 mm. Thus, copper nanoparticles synthesized using noni leaf extract bioreductor had the potential to be developed as an antibacterial agent for Streptococcus pyogenes.